A Case Report of Pneumosinus Dilatans of the Frontal Sinus and Review of the Literature - Hüseyin YAMAN et al.; Nermin AKKAN; Süleyman YILMAZ (Düzce Tıp Fakültesi Dergisi, 2010)
Pneumosinus dilatans is an extremely rare condition which is characterized by gross enlargementof the paranasal sinuses. The etiology is not identified. Pneumosinus dilatans refers to an aeratedsinus which is abnormally expanded. Anatomical variations of the paranasal sinuses and nasalcavity are important in sinus diseases. We are reporting one patient with pneumosinus dilatanswho attended Duzce medical faculty ENT department with severe headache. We considered asfrontonasal complex and septum deviation disease by the CT and endoscopic examinations, andtreated by functional endoscopic surgery and septoplasty surgery. Headache and nasalobstruction symptoms disappeared completely in the follow up period. Frontal sinus size isfollowed up by CT. Frontal sinus enlargement was seen with the preoperative paranasal CTwhich are taken consecutive years. Frontal sinus size reduction was evaluated 18 months aftersurgery with the control paranasal sinus CT examination.